2007
DOI: 10.1590/s1414-81452007000400008
|View full text |Cite
|
Sign up to set email alerts
|

O adolescente e as drogas: conseqüências para a saúde

Abstract: Pesquisa Documental. Objetivos: identificar a freqüência do uso/abuso de drogas pelos adolescentes escolares de instituição de ensino médio; e analisar as conseqüências do uso/abuso de drogas para a saúde do adolescente. Fontes: dois relatórios de pesquisas realizadas com esses adolescentes, no segundo semestre de 2006 e primeiro semestre de 2007. O estudo evidenciou o consumo do álcool como de grande destaque entre os pesquisados e mostrou, ainda, que aproximadamente 6% da população em estudo já teve contato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
7
0
9
Order By: Relevance
“…Therefore, the use of this substance can strengthen the idea of progression as the use of other licit and illicit drugs. Moreover, marijuana has a lower commercial value, which makes it more accessible to young people, especially those from low income families (5) , as it can be seen in our data on socioeconomic family income.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Therefore, the use of this substance can strengthen the idea of progression as the use of other licit and illicit drugs. Moreover, marijuana has a lower commercial value, which makes it more accessible to young people, especially those from low income families (5) , as it can be seen in our data on socioeconomic family income.…”
Section: Discussionmentioning
confidence: 76%
“…However, these are still controversial issues on these results that need further investigation. While some studies (1,6) indicate marijuana just as the second most popular illicit substance by secondary education students, another report (5) indicates that marijuana is the most used drug. The I National Household Survey on the Use of Psychotropic Drugs performed by CEBRID also reported that marijuana is the most illicit drug used in Brazil (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…É um fenômeno bastante antigo na história da humanidade e constitui um grave problema de saúde pública, com sérias consequências pessoais e sociais, levando ao aumento de criminalidade juvenil, de casos da insanidade mental e até de mutações genéticas em filhos dos jovens envolvidos em consumo de drogas [6,7]. Outro problema que sobressai é o combate ao seu tráfico [8][9][10].…”
Section: Introductionunclassified